Active case finding of tuberculosis in Europe: a Tuberculosis Network European Trials Group (TBNET) survey - Keane, Joseph (My University, 2008)
Tuberculosis control depends on successful case finding and treatment of individuals infected with Mycobacterium tuberculosis. Passive case finding is widely practised: the present study aims to ascertain the consensus and possible improvements in active case finding across Europe. Recommendations from national guidelines were collected from 50 countries of the World Health Organization European region using a standard questionnaire. Contacts are universally screened for active tuberculosis and latent tuberculosis infection (LTBI). Most countries (>70%) screen those with HIV infection, prisoners and in-patient contacts. Screening of immigrants is related to their contribution to national rates of tuberculosis. Only 25 (50%) out of 50 advise a request for symptoms in their guidelines. A total of 36 (72%) out of 50 countries recommend sputum examination for those with a persistent cough; 13 countries do not, even if the chest radiograph suggests tuberculosis. Nearly all countries (49 out of 50) use tuberculin skin testing (TST); 27 (54%) out of 50 countries also perform chest radiography irrespective of the TST result. Interpretation of the TST varies widely. All countries use 6–9 months of isoniazid for treatment of LTBI, with an estimated median (range) uptake of 55% (5–92.5%). Symptoms and sputum examination could be used more widely when screening for active tuberculosis. Treatment of latent tuberculosis infection might be better focused by targeted use of interferon-γ release assays.
Keywords: Active case finding; Contacts; Europe; Screening; Tuberculosis